2022
DOI: 10.1002/acm2.13604
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric evaluation of cone‐beam CT‐based synthetic CTs in pediatric patients undergoing intensity‐modulated proton therapy

Abstract: To evaluate dosimetric changes detected using synthetic computed tomography (sCT) derived from online cone-beam CTs (CBCT) in pediatric patients treated using intensity-modulated proton therapy (IMPT). Methods: Ten pediatric patients undergoing IMPT and aligned daily using proton gantry-mounted CBCT were identified for retrospective analysis with treated anatomical sites fully encompassed in the CBCT field of view. Dates were identified when the patient received both a CBCT and a quality assurance CT (qCT) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…To the best of our knowledge, all presently available studies on CBCT corrections either recalculated the pCT plan on the generated daily CTs and re‐CTs or created a new plan on re‐CT and further recalculated it on the generated daily CTs 6,8,32,33 . Such methods of recalculating plans on daily CTs may not have a substantial impact on the dose distribution if neighboring ROIs have HU values that are not considerably different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, all presently available studies on CBCT corrections either recalculated the pCT plan on the generated daily CTs and re‐CTs or created a new plan on re‐CT and further recalculated it on the generated daily CTs 6,8,32,33 . Such methods of recalculating plans on daily CTs may not have a substantial impact on the dose distribution if neighboring ROIs have HU values that are not considerably different.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, all presently available studies on CBCT corrections either recalculated the pCT plan on the generated daily CTs and re-CTs or created a new plan on re-CT and further recalculated it on the generated daily CTs. 6,8,32,33 Such methods of recalculating plans on daily CTs may not have a substantial impact on the dose distribution if neighboring ROIs have HU values that are not considerably different. This has been shown by Kurz et al 8 that despite a satisfactory agreement in terms of proton range and GPR analysis, detailed visual inspection and contour analysis of OARs found that the vCT is insufficiently accurate for prostate cancer patients.…”
Section: F I G U R Ementioning
confidence: 99%
“…There, higher gamma pass rates were seen which was expected due to the higher sensitivity of dose distributions in proton therapy compared to photon therapy. DIR has also been used in an in-house built sCT method tested on paediatric proton therapy patients [25] . Deep-learning has recently also attracted attention for sCT generation [13] , [26] , [27] , e.g.…”
Section: Discussionmentioning
confidence: 99%
“…28 Several evaluations have been conducted on the use of sCT in adaptive proton radiotherapy, with most of these studies utilizing deep convolutional neural network (DCNN) and cycleGAN to generate sCT. [29][30][31][32] In this study, we aim to assess the suitability of different deep learning models, including the newly proposed cGAN, Unet+cycleGAN, and the conventional Unet and cycleGAN models, for generating sCT in NPC. By analyzing their unique structures and characteristics,we can determine which model is more appropriate for sCT generation and holds potential for further clinical exploration in adaptive proton therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several evaluations have been conducted on the use of sCT in adaptive proton radiotherapy, with most of these studies utilizing deep convolutional neural network (DCNN) and cycleGAN to generate sCT 29–32 . In this study, we aim to assess the suitability of different deep learning models, including the newly proposed cGAN, Unet+cycleGAN, and the conventional Unet and cycleGAN models, for generating sCT in NPC.…”
Section: Introductionmentioning
confidence: 99%